Implementation of National Morals in Islamic Boarding Schools to Strengthen Religious Identity and Superior Character - Anwar, Cecep; Sobandi, Oban; Ihsan, Mahlil Nurul; Maliki, Sabila Nur (Laboratory of Islamic Religious Education Faculty of Tarbiyah and Teacher, 2024)
Pesantren has an important role in fostering the morals of the nation by strengthening religious identity and building superior character. In the era of the Industrial Revolution 4.0, which is dominated by digitalization and technological developments, moral challenges are increasingly urgent in building an ethical society. The purpose of this study is to examine the role of pesantren in fostering the nation's morals in this digital era. This research is included in library research, which is descriptive qualitative in nature. The results show that pesantren provide in-depth religious education to students, strengthen their religious identity, and teach strong moral values. In addition, pesantren also build superior character through a holistic education approach. They encourage the development of positive attitudes such as discipline, responsibility, honesty, hard work, and helping. Pesantren also provide leadership and social skills training to santri. This research resulted in an in-depth understanding of the strategic role of pesantren in fostering the nation's morals. The development of the nation's morals through pesantren contributes to creating a young generation that is technologically savvy, has integrity, and is able to contribute positively in building a civilized society.Â Pesantren memiliki peran penting dalam membina akhlak bangsa dengan memperkuat identitas keagamaan dan membangun karakter unggul. Dalam era Revolusi Industri 4.0 yang didominasi oleh digitalisasi dan perkembangan teknologi, tantangan moral semakin mendesak dalam membangun masyarakat yang beretika. Tujuan penelitian ini adalah untuk mengkaji peran pesantren dalam pembinaan akhlak bangsa di era digital ini. Penelitian ini termasuk ke dalam penelitian kepustakaan (library research), yang bersifat kualitatif deskriptif. Hasil penelitian menunjukkan bahwa pesantren memberikan pendidikan agama yang mendalam kepada santri, memperkuat identitas keagamaan mereka, dan mengajarkan nilai-nilai moral yang kuat. Selain itu, pesantren juga membangun karakter unggul melalui pendekatan pendidikan holistik. Mereka mendorong pengembangan sikap positif seperti kedisiplinan, tanggung jawab, kejujuran, kerja keras, dan tolong-menolong. Pesantren juga memberikan pelatihan kepemimpinan dan keterampilan sosial kepada santri. Penelitian ini menghasilkan pemahaman yang mendalam tentang peran strategis pesantren dalam membina akhlak bangsa. Pembinaan akhlak bangsa melalui pesantren berkontribusi dalam menciptakan generasi muda yang cerdas teknologi, berintegritas, dan mampu berkontribusi positif dalam membangun masyarakat yang beradab.